2021
DOI: 10.1007/s41062-021-00515-y
|View full text |Cite
|
Sign up to set email alerts
|

Design a smart infrastructure monitoring system: a response in the age of COVID-19 pandemic

Abstract: Since the end of 2019, COVID-19 has been a challenge for the world, and it is expected that the world must take precautionary steps to tackle the virus spreading prior produces an efficient vaccine. Currently, most government efforts seek to avoid disseminating the coronavirus and forecast probable hot areas. The most susceptible to coronaviral infection are the healthcare staff due to their daily contact with potential patients. This article proposes a COVID-19 real-time system for tracking and identifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…During the Covid-19 pandemic, an attack named Covid-Lock appears as a malicious app that requires bitcoin to recover the end user's phone. The threat which made users worry was the leakage of personal data or deletion of the whole phone data [112]. Similarly, if an end-user creates a backup of their smartphone's data, it can be hacked on the base of a trojan horse attack too.…”
Section: Spam Emailsmentioning
confidence: 99%
“…During the Covid-19 pandemic, an attack named Covid-Lock appears as a malicious app that requires bitcoin to recover the end user's phone. The threat which made users worry was the leakage of personal data or deletion of the whole phone data [112]. Similarly, if an end-user creates a backup of their smartphone's data, it can be hacked on the base of a trojan horse attack too.…”
Section: Spam Emailsmentioning
confidence: 99%
“…e results showed that the system achieves 99.9% accuracy in the range of (500 ± 5) cm [2]. Imoize et al researched sustainable social intelligence infrastructure supporting 6G, introduced the evolution background of different wireless communication standards and emerging 6G applications such as multisensory extended reality and digital replication.…”
Section: Related Workmentioning
confidence: 99%
“…One of the distinctive features of the paper is combination of various Internet of Things (IoT) sensing. While many of the solutions rely on massive testing, wearable devices, and other intrusive methods or do not provide timely identification of threats and response [22][23][24][25], this study proposes to combine various sensing technologies to achieve timely and non-intrusive detection of infection threats and to enact suitable response mechanisms. The paper is structured as follows: Section 2 presents the air quality sensors review, calibration specifics of commercially available sensors, including details of the operation of ventilation systems and sensors placement.…”
Section: Introductionmentioning
confidence: 99%